The Subject of Male Hysteria and Male Masochism in David Fincher’s Fight Club - CHOURDAKI, VOULA (Advances in Social Sciences Research Journal, 2019)
The current research paper explores the various themes found in David Fincher’s 1999 film Fight Club with a focus upon the subject of male hysteria and male masochism as shown through the main character’s point of view. The fear of metaphorical emasculation in the contemporary materialistic and capitalistic society, the identity crisis as well as the notion of physical violence as a means against all threats to masculinity are thoroughly discussed and interrelated. What this paper also attempts to look at is the duality of self, gender and sexuality stereotypes and the delusional expectations the modern individual has acquired which lead the latter to total paranoia and inner/outer chaos; all seen through the eyes of the film’s director and protagonist.